National Youth Policy 2017-2018 Jamaica: Popular Version - National Youth Policy Working Group (My University, 2019)
The vision, goals and strategies of the National Youth Policy (20172030) are based on the personal experiences and expectations of Jamaica’s youth, and an analysis of issues affecting our young people. The National Youth Policy contains the following key points: 1. The importance of youth and youth development 2. A true understanding of the challenges our youth face on a daily basis 3. Guiding Principles 4. National Commitments 5. Policy Priorities 6. The Goals and Strategic objectives of the policy: What does the policy aim to do? 7. Monitoring and Evaluation mechanism to track the success of the policy.
Developed by the National Youth Policy Working Group supported by the Youth and Adolescent Policy Division within the Ministry of Education
Keywords: youth policy; youth development